Buku kedominikanan : Untuk TK B Semester 1 & 2 /Sr. Rosiana, Rosalina Yani, Sr. Andrea ; editor Sr. M. Serafine...[et.all] ; ilustrator, Robert - ROSIANA, Sr.; Rosalina Yani; Andrea, Sr; Serafine, Sr. M; Robert (St. Dominic Publishing, 2015)
x, 100 hlm. : ilus. ; 24 cm.